Combination of transient elastography with serum-based non-invasive tests improves prediction of liver fibrosis in patients with chronic hepatitis C: a prospective cohort study - Zykus, Romanas; Jonaitis, Laimas; Petrenkienė, Vitalija; Gudinavičienė, Inga; Kupčinskas, Limas (Acta medica Lituanica, 2015)
The work was carried out at the Lithuanian University of Health Sciences Hospital Kaunas Clinics. Background. To date, there is not enough data to conclude whether the combination of different non-invasive liver fibrosis tests could improve the accuracy in prediction of liver fibrosis. The aim of this study was to assess correlation between transient elastography (TE), aspartate aminotransferase to platelet ratio index (APRI), fibrosis 4 score (FIB4) and histological stage of fibrosis (F). Materials and methods. In this prospective study the correlation of TE, APRI and FIB4 with the stage of fibrosis was assessed in 140 patients with chronic HCV hepatitis. TE, APRI and FIB4 were measured the same day before biopsy. Fibrosis was evaluated using the METAVIR score. Cut-off values were established by applying the ROC curve analysis. All non-invasive tests were combined into pairs in order to evaluate the accuracy of fibrosis prediction. Results. The stage of fibrosis correlated with TE (R-0.74), FIB4 (R-0.67) and APRI (R-0.58). To detect F4 TE cut-off value 12.1 kPa had 93.8% sensitivity and 85% specificity; APRI cut-off value 1.42 (84.4/81.1) and FIB4 cutoff value 2.89 (84.4/84.0) were established. To determine F ≥ 3 – 10.3 kPa (91.1/83.9), 1.28 (77.8/78.5), 2.28 (84.4/81.7); F ≥ 2 8.5 kPa (80.9/74.3), 1.12 (72.1/78.6), 1.63 (82.4/75.7); F  ≥  1 5.35  kPa (85.4/100), 0.45 (89.2/87.5), 0.89 (87.7/75). Significant increase of accuracy was observed in TE/APRI (p – 0.008) and FIB4/APRI (p – 0.02) groups to predict F ≥ 1, and TE/FIB4 to predict F ≥ 2 (p – 0.04) and F ≥ 1 (p – 0.04). Conclusions. Combined use of TE/APRI, FIB4/APRI increased the accuracy to predict F ≥ 1, and TE/FIB4 combination increased the accuracy to predict F ≥ 2 and F ≥ 1.
Keywords: transient elastograhy; APRI; FIB4; liver fibrosis; combinations